Effect of MnO2 coating on layered Li(Li0.1Ni0.3Mn0.5Fe0.1)O2 cathode material for Li-ion batteries - Uzun, Davut; Dogrusoz, Mehbare; Mazman, Muhsin; Bicer, Emre; Avci, Ercan; Sener, Tansel; Kaypmaz, Tevhit Cem (Elsevier Science Bv, 2013)
A new nanosized, cobalt free, iron containing and non-toxic layered Li(Li0.1Ni0.3Mn0.5Fe0.1)O-2 cathode material was synthesized by solid-state reaction method and further MnO2 coating procedure was applied to Li(Li0.1Ni0.3Mn0.5Fe0.1)O-2 in order to improve charge/discharge and cycle properties. The effect of MnO2 coating on the capacity and rate capability of cathode active material was described in detail by galvanostatic charge/discharge cycles. Although the initial discharge capacities at a 0.1 C rate were very close at the first discharge as 210 mAh g(-1) for MnO2 coated Li(Li0.1Ni0.3Mn0.5Fe0.1)O-2 and 205 mAh g(-1) for uncoated Li(Li0.1Ni0.3Mn0.5Fe0.1)O-2, respectively, later it was proven that the MnO2 coated cathode active material shows better discharge capacities at faster regimes. The improvement is based on the highly ionic conductive MnO2 coating layer, which suppresses solid electrolyte interface growth during the battery operation. Discharge capacities at 0.1 C rate of uncoated and MnO2 coated layered Li(Li0.1Ni0.3Mn0.5Fe0.1)O-2 cathode materials at the 100th cycle were obtained at 139 and 175 mAh g(-1), respectively. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: NMF; Iron-substituted; Lithium rich; MnO2 coating; Li-ion battery